Antioxidant activity and phenolic compounds of vitex trifolia var,simplicifolia associated with anticancer - Aweng Eh Rak; Nur Hanisah; Mohd Nawi M.A; Nurhanan Murni Y (2012)
Vitex trifolia var.simplicifolia plant was found growing wildly at the beach, especially at Pantai Sri Tujuh, Tumpat, Kelantan, Malaysia. The extracted leaves were commonly used to prepare traditional dessert among Siamese communities in Kelantan called “Khanom Bai Kunthi” for a long time. Water was used as an extraction agent by the peoples in this area. This extracted leaves were used by the Siamese communities in Tumpat area because it has natural color, flavor and fragrance properties. The Siamese communities who consumed “Khnom Bai Kunthi” was found to be healthy life and live longer. This is the starting point of the study. For the purpose of this study, Vitex trifolia var.simplicifolia leaves were extracted by using 80% methanol in the laboratory. The extracted V. trifolia var.simplicifolia was analyzed and found to be high in antioxidant activity of phenolic compound. The result shows that the extracted V. trifolia var. simplicifolia had high amount of total phenolic compound (44.66μg of GAE/mg of fresh weight). The plants secondary metabolites normally play role in cancer treatment. Cytotoxicity activity of the extracted V. trifolia var.simplicifolia was evaluated on MCF-7 (Breast cancer cell line), HT-29 (colorectal cancer cell line), and WRL-68 (normal liver cell line), and the results show that, cytotoxicity activity (IC50 values 78.87μg/ml, 77.50μg/ml, and 78.29μg/ml, respectively).